2017
DOI: 10.1161/jaha.117.005965
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Kcna2 Antisense RNA Contributes to Ventricular Arrhythmias via Silencing Kcna2 in Rats With Congestive Heart Failure

Abstract: BackgroundCongestive heart failure (CHF) is a common cardiovascular disease that is often accompanied by ventricular arrhythmias. The decrease of the slow component of the delayed rectifier potassium current (IK s) in CHF leads to action potential (AP) prolongation, and the IK s is an important contributor to the development of ventricular arrhythmias. However, the molecular mechanisms underlying ventricular arrhythmias are still unknown.Methods and ResultsKcna2 and Kcna2 antisense RNA (Kcna2 AS) transcript ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 58 publications
(86 reference statements)
0
34
0
1
Order By: Relevance
“…Overexpression of MALAT1 was shown to reduce miR-200c levels, leading to increased expression of high-mobility group box 1 (HMGB1), which decreased expression levels of Kv4.2 and Kv4.3 ion channels, dysregulating cardiac transient outward currents (I to ) [ 90 , 118 ]. LncRNA Kcna2-AS was found to contribute to ventricular arrhythmias [ 91 ]. Kcna2-AS is a negative regulator of Kcna (encoding Kv1.2 potassium channel), which helps control heart rate as well as performing several other physiological functions.…”
Section: Lncrnas and Their Interventions In Heart Diseasementioning
confidence: 99%
“…Overexpression of MALAT1 was shown to reduce miR-200c levels, leading to increased expression of high-mobility group box 1 (HMGB1), which decreased expression levels of Kv4.2 and Kv4.3 ion channels, dysregulating cardiac transient outward currents (I to ) [ 90 , 118 ]. LncRNA Kcna2-AS was found to contribute to ventricular arrhythmias [ 91 ]. Kcna2-AS is a negative regulator of Kcna (encoding Kv1.2 potassium channel), which helps control heart rate as well as performing several other physiological functions.…”
Section: Lncrnas and Their Interventions In Heart Diseasementioning
confidence: 99%
“…In the literature, lncRNAs were reported to play a role in cardiac development and regeneration, in the pathogenesis of cardiovascular diseases, as well as in the doxorubicin-induced cardiac toxicity, which predisposes people to DCM [48][49][50]. Furthermore, disrupted splicing of lncRNAs were found to cause dysregulation of important cardiac proteins in mice, such as potassium voltage-gated channel proteins encoded by Kcnq1 and Kcna2 [51][52][53]. In addition, a cluster of antisense lncRNAs in the MYH7 locus was noticed to be essential in early development of cardiomyopathy under pressure-overload [54].…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus genes and advancement. KCNE5 [45], SHANK3 [46], CASQ2 [47], EDNRA (endothelin receptor type A) [48], EPHB4 [49], ALPK3 [50], WNT11 [51], IRAK2 [52], FBN1 [53], SFRP2 [54], CLCA2 [55], NEXN (nexilin F-actin binding protein) [56], PALLD (palladin, cytoskeletal associated protein) [57], DAB2 [58], NRP2 [59], THBS2 [60], CSF1R [61], KCNA2 [62], CACNA1C [63], F2R [64], UCHL1 [65], CCL18 [66], ITGB1BP2 [67] and FMOD ( bromodulin) [68] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%